Deliniasi risiko iklim dan evaluasi model hubungan curah hujan dan produksi padi dalam mendukung pengembangan asuransi indeks iklim (climate index insurance) pada sistem usahatani berbasis padi - Woro Estiningtyas; Rizaldi Boer; Irsal Las; Agus Buono; Adi Rakhman (Jurnal Ilmu Pertanian Indonesia, 2011)
The agricultural sector, particularly the rice farming system (SUT) is very vulnerable to climate variability and change. SUT that rely heavily on water will be easily affected by climate variability and change when the water supply deficit of needs that should be. SUT is still dominant in the food supply in Indonesia, so the shock of farming due to extreme climate events will have a major impact on food security. Many findings indicate that the frequency and intensity of extreme climate events will increase as a result of global warming. Extreme climate events dominant occur in center of rice production in West Java like Indramayu is drought. Approximately 80°/o of the causes of the rice harvest failed in the district of Indramayu is the incidence of droughts. Farmers as the main actors receive large impacts due to drought is expected to be increasingly difficult to develop the farm. It is therefore necessary to have protection program for farmers from the impact of climate events such climate extrim. One option is starting a lot of feasibility is Climate Index Insurance. This study aimed to assess the feasibility of the implementation of the climate index insurance system in Indramayu. Analysis step is performed include (i) preparation of endemic drought maps are required as the basis in determining the priority areas of climate risk management and (ii) the determination of climate index value (threshold value) to be used as an index into the determination of the value of insurance claims. This study found that climate indices that can be used for the three villages at high risk of drought is high rainfall during the dry season. Index value for the three villages is 168 mm, 248 mm and 472 mm for Cikedung, lelea and Terisi. Potential applications of Climate Index Insurance for rice SUT in Indramayu is high because about 90°/o of the people are rice farmers. Besides benefit of rice farming is also quite large with B/C from 1.4 to 1.8 during the wet season and 1.2 to 1.7 on the dry season, so the expected ability to pay insurance premiums high enough.